Language-Learner Computer Interactions Theory, methodology and CALL applications - Caws, Catherine; Hamel, Marie-Josée (John Benjamins Publishing Company, 2016)
This book focuses on learner-computer interactions (LCI) in second language learning environments drawing largely on sociocultural theories of language development. It brings together a rich and varied range of theoretical discussions and applications in order to illustrate the way in which LCI can enrich our comprehension of technology-mediated communication, hence enhancing learners' digital literacy skills. The book is based on the premise that, in order to fully understand the nature of language and literacy development in digital spaces, researchers and practitioners in linguistics, sciences and engineering need to borrow from each others' theoretical and practical toolkits. In light of this premise, themes include such aspects as educational ergonomics, affordances, complex systems learning, learner personas and corpora, while also describing such data collecting tools as video screen capture devices, eye-tracking or intelligent learning tutoring systems.